Dynamic Transformation Mechanism for Producing Ultrafine Grained Steels. Issue 7 (9th March 2018) - Zhao, Lijia; Park, Nokeun; Tian, Yanzhong; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract : Ultrafine grained (UFG) steels with grain sizes around 1 micron exhibit an excellent strength‐ductility combination and have been extensively studied worldwide. Among the different grain refinement strategies, thermomechanical controlled processing (TMCP) employing dynamic transformation (DT), that is, ferrite transformation during deformation of austenite, is considered as the simplest and commercially exploitable approach to produce ultrafine ferrite (UFF) with grain size of a couple of microns or below. The present paper reviews the research history of DT and highlights the major aspects of continuous interest including the methods and evidences for identifying DT, thermodynamics and kinetics of DT, mechanism for UFF formation and the effects of some key thermomechanical parameters on DT (and UFF formation), together with an outlook for the future research, and new TMCP design for industrial application. This paper also discusses some areas remaining under debate such as the diffusional or displacive mechanism, thermodynamic modeling, and the mechanism for UFF formation, etc. Abstract : Dynamic transformation (DT) is a phenomenon that ferrite transformation occurs during the deformation of austenite. Ultrafine grained (UFG) steels with grain sizes around 1 micron can be produced by DT mechanism in a simple thermomechanical process without applying very high‐strain deformation, and have an excellent strength‐ductility combination as well as low ductile‐brittle transition temperature (DBTT), suggesting large commercialization potential.